Wavefront dislocations reveal the topology of quasi-1D photonic insulators - Clément Dutreix (Nature Portfolio, 2021)
Topological properties are defined from singularities of the wave functions delocalised in the bulk of the material, but most experimental manifestations remain indirect. Here, the authors observe a wavefront dislocation as a direct evidence of the phase singularity of the delocalised wave functions in 1D microwave photonic insulators.